HUBUNGAN FREKUENSI DAN LAMA LATIHAN TERHADAP FUNGSI KOGNISI (MEMORI) PENARI MODERN - Abdian Purnapita Pambudi; Dona Marisa; Asnawati Asnawati (Homeostasis, 2019)
Abstract: Cognition is the ability to recognize / know objects, circumstances or situations, which are associated with learning and intelligence. Cognition includes memory, concentration or attention, orientation, language skills, numeracy, visuospatial, executive functions, abstraction, and levels of intelligence. In this study, the intended cognition is memory related to the learning process of dance movements during modern dance practice. The higher frequency and duration of training will have possitive impact on the ability of the cognitive function (memory). This study aims to determine the relationship of frequency and duration of training to the function of cognition (memory) of modern dancers in Banjarmasin. This study used an observational analytic method with a crossectional approach. A sample of 30 people were taken by proportional stratified random sampling technique. Data analysis using Chi square test with level of confidence 95%. The results were obtained for the relationship between exercise frequency and cognition function (memory) with ρ value=0.001 (ρ <0.05) and the length of training relationship and cognitive function (memory) with ρ value=0.029 (ρ <0.05). The conclusion of this study shows that there is a significant relationship between the frequency and duration of training on the function of cognition (memory) of modern dancers in Banjarmasin. Keywords:frequency of training, duration of training, cognitive function, memory, modern dancers. Abstrak: Kognisi adalah kemampuan untuk mengenal/mengetahui benda, keadaan atau situasi, berhubungan dengan pembelajaran dan intelejensi.Kognisi meliputi memori atau daya ingat, konsentrasi atau perhatian, orientasi, kemampuan berbahasa, berhitung, visuospatial, fungsi eksekutif, abstraksi, dan taraf intelejensi.Pada penelitian ini, kognisi yang dimaksud adalah memori yang berkaitan dengan proses pembelajaran gerakan tari selama latihan tari modern. Frekuensi dan lama latihan yang semakin tinggi akan berdampak pada kemampuan fungsi kognisi (memori) yang baik. Penelitian ini bertujuan untuk mengetahui hubungan frekuensi dan lama latihan terhadap fungsi kognisi (memori) penari modern di Banjarmasin. Penelitian ini menggunakan  metode observasional analitik  dengan pendekatan cross sectional. Sampel sebanyak 30 orang diambil dengan teknik proportional stratified random sampling. Analisis data menggunakan uji Chi square dengan tingkat kepercayaan 95%. Hasil penelitian didapatkan untuk hubungan frekuensi latihan dan fungsi kognisi (memori) ρ value=0,001 (ρ < 0,05) dan hubungan lama latihan dan fungsi kognisi (memori) ρ value=0,029 (ρ< 0,05). Kesimpulan dari penelitian ini menunjukkan adanya hubungan yang bermakna antara frekuensi dan lama latihan terhadap fungsi kognisi (memori) penari modern di Banjarmasin. Kata-kata kunci: frekuensi latihan, lama latihan, fungsi kognisi, memori, penari modern.Abstract:Cognition is the ability to recognize / know objects, circumstances or situations, which are associated with learning and intelligence. Cognition includes memory, concentration or attention, orientation, language skills, numeracy, visuospatial, executive functions, abstraction, and levels of intelligence. In this study, the intended cognition is memory related to the learning process of dance movements during modern dance practice. The higher frequency and duration of training will have possitive impact on the ability of the cognitive function (memory). This study aims to determine the relationship of frequency and duration of training to the function of cognition (memory) of modern dancers in Banjarmasin. This study used an observational analytic method with a crossectional approach. A sample of 30 people were taken by proportional stratified random sampling technique. Data analysis using Chi square test with level of confidence 95%. The results were obtained for the relationship between exercise frequency and cognition function (memory) with ρ value=0.001 (ρ <0.05) and the length of training relationship and cognitive function (memory) with ρ value=0.029 (ρ <0.05). The conclusion of this study shows that there is a significant relationship between the frequency and duration of training on the function of cognition (memory) of modern dancers in Banjarmasin. Keywords:frequency of training, duration of training, cognitive function, memory, modern dancers. Abstrak: Kognisi adalah kemampuan untuk mengenal/mengetahui benda, keadaan atau situasi, berhubungan dengan pembelajaran dan intelejensi..Kognisi meliputi memori atau daya ingat, konsentrasi atau perhatian, orientasi, kemampuan berbahasa, berhitung, visuospatial, fungsi eksekutif, abstraksi, dan taraf intelejensi.Pada penelitian ini, kognisi yang dimaksud adalah memori yang berkaitan dengan proses pembelajaran gerakan tari selama latihan tari modern. Frekuensi dan lama latihan yang semakin tinggi akan berdampak pada kemampuan fungsi kognisi (memori) yang baik. Penelitian ini bertujuan untuk mengetahui hubungan frekuensi dan lama latihan terhadap fungsi kognisi (memori) penari modern di Banjarmasin.Penelitian ini menggunakan  metode observasional analitik  dengan pendekatan cross sectional. Sampel sebanyak 30 orang diambil dengan teknik proportional stratified random sampling. Analisis data menggunakan uji Chi square dengan tingkat kepercayaan 95%. Hasil penelitian didapatkan untuk hubungan frekuensi latihan dan fungsi kognisi (memori) ρ value=0,001 (ρ < 0,05) dan hubungan lama latihan dan fungsi kognisi (memori) ρ value=0,029 (ρ< 0,05). Kesimpulan dari penelitian ini menunjukkan adanya hubungan yang bermakna antara frekuensi dan lama latihan terhadap fungsi kognisi (memori) penari modern di Banjarmasin. Kata-kata kunci: frekuensi latihan, lama latihan, fungsi kognisi, memori, penari modern